Early Warning Signals in Phase Space: Geometric Resilience Loss Indicators From Multiplex Cumulative Recurrence Networks - Hasselman, Fred (Frontiers in Physiology, 2022)
The detection of Early Warning Signals (EWS) of imminent phase transitions, such as sudden changes in symptom severity could be an important innovation in the treatment or prevention of disease or psychopathology. Recurrence-based analyses are known for their ability to detect differences in behavioral modes and order transitions in extremely noisy data [@bianciardi2007a; @shockley2002a; @zbilut1998a]. As a proof of principle, the present paper provides an example of a recurrence network based analysis strategy which can be implemented in a clinical setting in which data from an individual is continuously monitored for the purpose of making decisions about diagnosis and intervention. Specifically, it is demonstrated that measures based on the geometry of the phase space can serve as Early Warning Signals of imminent phase transitions. A publicly available multivariate time series is analysed using so-called cumulative Recurrence Networks (cRN), which are recurrence networks [@zou2019a] with edges weighted by recurrence time and directed towards previously observed data points. The results are compared to previous analyses of the same data set [@cramer2016a], benefits, limitations and future directions of the analysis approach are discussed.